O USO DE SIMULAÇÕES INTERATIVAS PHET NO ENSINO DE FRAÇÕES - Makuch, Franciele do Belém (2016)
He tried to take action to contribute to the solution of one of the commonly identified educational problems in the school setting of the second primary education cycle in Mathematics, which is the fractions of Education. So, there was this work, from the following question: What contributions using interactive simulations PhET can bring to teaching fractions? Situated within the qualitative research, this study consisted of a practical action-research, ie, research conducted concurrently to an action aimed at solving a problem learning. Their goal was to explore the potential of interactive simulations PhET Simulations in the development of activities related to fractions of Education. The research was developed through participant observation and pedagogical intervention in two rooms of support for learning mathematics, in Guarapuava. With the need for alternative teaching methodologies, we opted for the approach to Problem Solving and Technology Media - current methodological trends in mathematics education. As a technological tool, it was considered the use of PhET - characterized by the development of simulations mediated problem situations. This proposal achieved its objectives, therefore, was well received by teachers and students involved, agreeing with the need for alternative methodologies in support rooms in the content of fractions. He approached the reality of the students, to the extent that the technologies are present in their daily lives, and contemplated multi representational aspects, dynamic graphics, simulations, and interdisciplinary contexts in learning situations. It was concluded that most students could develop, building knowledge related to fractions.